Gene profiling of canine B-cell lymphoma reveals germinal center and post-germinal center subtypes with different survival times, modeling human DLBCL - Richards, Kristy L. (2013)
Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoma subtype, and fewer than half of patients are cured with standard front-line therapy. To improve therapeutic options, better animal models that accurately mimic human DLBCL (hDLBCL) are needed. Canine DLBCL (cDLBCL), one of the most common cancers in veterinary oncology, is morphologically similar to hDLBCL and is treated using similar chemotherapeutic protocols. With genomic technologies, it is now possible to molecularly evaluate dogs as a potential large-animal model for hDLBCL. We evaluated canine B-cell lymphomas (cBCLs) using immunohistochemistry and gene expression profiling. Canine B-cell lymphoma expression profiles were similar in many ways to hDLBCLs. For instance, a subset had increased expression of NF-κB pathway genes, mirroring human activated B-cell (ABC)-type DLBCL. Furthermore, immunoglobulin heavy chain (IGH) ongoing mutation status, which is correlated with ABC/germinal center B-cell (GCB) cell of origin in hDLBCL, separated cBCL into two groups with statistically different progression-free and overall survival times. In contrast with hDLBCL, cBCL rarely expressed BCL6 and MUM1/IRF4 by immunohistochemistry. Collectively, these studies identify molecular similarities to hDLBCL that introduce pet dogs as a representative model of hDLBCL for future studies, including therapeutic clinical trials.